Pengelompokan Kejadian Stunting di Indonesia pada Tahun 2022 dan Faktor-faktor yang Memengaruhinya: Sebuah Gambaran - Putri, Aida Devanty; Maulidia, Sopa (Politeknik Statistika STIS, 2024)
Stunting can have a significant impact on the development of human resources in Indonesia. This condition can be a threat to achieving sustainable development. This study aimed to clustering the incidence of stunting and analyze its determinants based on the direct causes of stunting. The data we uses come from Statistics Indonesia and the Ministry of Health’s SSGI report 2022. We perform a clustering analysis using k-means method for descriptive analysis while inferential analysis is described through multiple linear regression model. The result of the study show that there are two clusters formed and three variables that significantly affect the incidence of stunting in Indonesia, which are Low Birth Weight (BBLR), Access to Safe and Appropriate Sanitation, and Complete Immunization. The findings of this study are expected to provide a robust scientific basis for the development of more efficient health policies and programs aimed at reducing stunting in Indonesia.